The influence between proactive personality, basic psychological needs, and entrepreneurial motivation: An empirical study of students majoring in entrepreneurship management in Hong Kong - Sheng, Chen; Hong, Yun Li; Wei, Kong Xiao (Journal of Accounting, Business and Finance Research, 2026)
Entrepreneurs are central to economic innovation and growth, yet complex interactions between personality traits and psychological needs shape their motivations. This study investigates the relationship between proactive personality, basic psychological needs, and entrepreneurial motivation among postgraduate students majoring in entrepreneurship management in Hong Kong. Using survey data from 163 students (138 valid responses), multiple regression analysis was conducted to examine causal links between these variables. Results reveal significant associations, underscoring the importance of proactive personality and psychological needs in fostering entrepreneurial motivation. These findings provide valuable implications for educators and policymakers seeking to cultivate entrepreneurial potential and strengthen the entrepreneurial ecosystem.